2009
DOI: 10.1016/j.yexcr.2008.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Gravin dynamics regulates the subcellular distribution of PKA

Abstract: Gravin, a multivalent A-kinase anchoring protein (AKAP), localizes to the cell periphery in several cell types and is postulated to target PKA and other binding partners to the plasma membrane. An N-terminal myristoylation sequence and three regions rich in basic amino acids are proposed to mediate this localization. Reports indicating that phorbol ester affects the distribution of SSeCKS, the rat orthologue of gravin, further suggest that PKC may also regulate the subcellular distribution of gravin, which in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 46 publications
3
47
0
Order By: Relevance
“…Gravin-EGFP, gravin-V5/His, (ΔCB4) gravin-EGFP, and PKA RII-ECFP were constructed and described previously [7, 9]. This study utilized four additional gravin constructs which were made as follows: A mutant gravin construct termed “(mutCB4) gravin-EGFP” was generated with three substitutions in the CB4 domain which replaced valine 672, valine 676, and leucine 681 each with alanine (V672A, V676A, L681A) using site-directed mutagenesis (Phusion®, New England Biolabs, product F-541; forward primer 5′ C ATCTTGGGAAGCT GC AATTTGTGTG; reverse primer 5′CTGAGGTATCC G CCTT T CGCTTTGGT; mutagenic nucleotides underlined).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gravin-EGFP, gravin-V5/His, (ΔCB4) gravin-EGFP, and PKA RII-ECFP were constructed and described previously [7, 9]. This study utilized four additional gravin constructs which were made as follows: A mutant gravin construct termed “(mutCB4) gravin-EGFP” was generated with three substitutions in the CB4 domain which replaced valine 672, valine 676, and leucine 681 each with alanine (V672A, V676A, L681A) using site-directed mutagenesis (Phusion®, New England Biolabs, product F-541; forward primer 5′ C ATCTTGGGAAGCT GC AATTTGTGTG; reverse primer 5′CTGAGGTATCC G CCTT T CGCTTTGGT; mutagenic nucleotides underlined).…”
Section: Methodsmentioning
confidence: 99%
“…In response to either PKC activation or intracellular calcium ([Ca 2+ ] i ) elevation, gravin is redistributed away from the membrane along with PKA that is bound to gravin. Gravin redistribution by PKC activation was shown by Yan et al [7] to redirect gravin and PKA to a juxtanuclear vesicular compartment. In response to [Ca 2+ ] i elevation, Tao et al [8] showed that gravin redistributes to the cytosol through a mechanism thought to involve Ca 2+ /calmodulin binding to gravin’s membrane-associated polybasic domains, PB1-3.…”
Section: Introductionmentioning
confidence: 99%
“…Given that SSeCKS is an in vitro and in vivo PKC substrate (26,32,44) and that short term PMA treatment induces a co-translocation of SSeCKS and actin fibers to the perinucleus (32,36,45), we addressed whether KO-MEF were defective in PMA-induced PKC translocation, cytoskeletal remodeling, and cell rounding. Although KO-MEF exhibit increased PMA-induced PKC activation (Fig.…”
Section: Pkc-binding Domainmentioning
confidence: 99%
“…AKAP-RII subcellular localization can be changed by Ca 2+ and PKC, notably from the plasma membrane to the cytoplasm (Yan et al 2009;Schott and Grove 2013). This redistribution, in Figure 4.…”
Section: Alteration Of a Memory Tracementioning
confidence: 91%